Interactive teleconferencing combining Spatial Audio Object Coding and DirAC technology - Herre, Jürgen; Falch, Cornelia; Mahne, Dirk; Del Galdo, Giovanni; Kallinger, Markus; Thiergart, Oliver (Journal of the Audio Engineering Society, 2011)
The importance of telecommunication continues to grow in our daily lives. An ambitious goal for developers is to provide the most natural means of audio communication by giving users the perception of being located next to each other. MPEG Spatial Audio Object Coding (SAOC) is a technology for coding, transmitting, and interactively reproducing spatial sound scenes on any conventional multi-loudspeaker setup (e.g., ITU 5.1). This paper describes how Directional Audio Coding (DirAC) can be used as a recording front end for SAOC-based teleconferencing systems, capturing acoustic scenes and extracting the individual objects (talkers). By introducing a novel DirAC to SAOC parameter transcoder, a highly efficient way of combining both technologies is presented which enables interactive, object-based spatial teleconferencing.
herre_books_journals